2019
DOI: 10.18632/aging.101733
|View full text |Cite
|
Sign up to set email alerts
|

Leonurine ameliorates D-galactose-induced aging in mice through activation of the Nrf2 signalling pathway

Abstract: Aging is a complex physiological phenomenon associated with oxidative stress damage. The objective of this study was to investigate the potential effects of leonurine on D-galactose-induced aging in mice and its possible mechanisms. In this study, we first tested the antioxidant activity of leonurine in vitro. A subcutaneous injection of D-galactose in mice for 8 weeks was used to establish the aging model to evaluate the protective effects of leonurine. The results showed that treatment with 150 mg·kg-1 leonu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 68 publications
(65 reference statements)
5
30
0
Order By: Relevance
“…Our further investigations indicated that AOS supplementation potently activated the Nrf2 signaling pathway by increasing the Nrf2 transcription level and facilitated the expression of the Nrf2 downstream target genes HO-1 and NQO1 in aging model mice. These results are in line with those of previous studies [ 7 , 47 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our further investigations indicated that AOS supplementation potently activated the Nrf2 signaling pathway by increasing the Nrf2 transcription level and facilitated the expression of the Nrf2 downstream target genes HO-1 and NQO1 in aging model mice. These results are in line with those of previous studies [ 7 , 47 ].…”
Section: Discussionsupporting
confidence: 94%
“…The antioxidant defense system has been proven to play a major role in senescence by regulating intracellular redox balance [ 6 ]. Therefore, resistance to oxidative stress may be a promising therapeutic strategy for delaying the kidney aging process [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of Nrf2 signaling could lead to ROS production and oxidative injury [ 21 , 33 , 34 ]. By measuring CellROX fluorescence [ 35 , 36 ], we show that XL388 induced significant ROS production in A172 cells ( Figure 4D ).…”
Section: Resultsmentioning
confidence: 99%
“…In D-gal-induced aging rat model, the excessive and long-term injection of D-gal can lead to the overproduction of AGEs and ROS, which may result strong oxidative stress and chronic inflammation that accelerates aging in rats [9][10][11][12][13]. Chronic, aseptic, and low-degree inflammation was considered a sign of the aging process [2].…”
Section: Discussionmentioning
confidence: 99%
“…Excessive long-term D-gal intake can lead to the overproduction of advanced glycosylation end-products (AGEs) and reactive oxygen species (ROS) [5], which may contribute to chronic inflammation and oxidative stress [6]. Many studies have shown that chronic inflammation and oxidative stress would result in mitochondrial, neurological function damage, and even cognitive decline [7][8][9][10][11][12]. The model of accelerated aging with long-term injection of D-gal has been widely used in antiaging studies, due to the increase of chronic inflammation, decline of cognition, and biochemical indexes that are similar with natural aging in animals [5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%